A Pilot Study Investigating the Impact of High Altitude on Myostatin and Irisin Levels - Rathor, Richa; Suryakumar, Geetha; Singh, Somnath (Defence Life Science Journal, 2024)
Many people visit and stay at high altitude due to adventure or occupation. The high-altitude environment comprises many factors alien to sea residents and detrimental to physical and mental health. Myokines are peptides and cytokines secreted from muscles and have a prime role in regulating skeletal muscle growth and myo-degradation. Therefore, the present study investigated the function of myokines in regulating muscle mass during acute and chronic high-altitude exposure. The study was conducted on Indian healthy subjects (n=29) who were distributed into three groups: Control (sea level (SL; n=15), acute high altitude stayed subjects (stayed at high altitude for less than ten days (AHA; n=7); chronic high altitude stayed subjects (stayed at high altitude for 15 days to 3 months (CHA; n=7). Acute exposure to high altitude leads to an increase in myostatin levels, indicating enhanced myo-degradation. Irisin levels were also increased in AHA group compared to SL group, depicting inclined myogenesis. However, CHA group showed an increase in myostatin levels but a non-significant change in irisin content in relation to SL group, suggesting enhanced myo-degradation. These findings generated a unique role of myokines, including myostatin and irisin, in managing skeletal muscle health with reference to high altitude.